Scaling up orange-fleshed sweetpotato through agriculture and nutrition (SUSTAIN) in Mozambique - Brouwer, R.; Queiroz, M. (International Potato Center, 2015)
SUSTAIN is a 5-year partnership (2013-2018), coordinated by CIP and financed by the UK Department for International Development, to scale up the nutrition benefits of biofortified orange-fleshed sweetpotato (OFSP). The goal is to reach 1.2 million households with under-5 year old children in Kenya, Malawi, Mozambique, and Rwanda. SUSTAIN supports integrated interventions in agriculture, nutrition, utilization, and marketing to strengthen production and consumption of OFSP. This flyer captures the work in Mozambique during the period June 2014 - July 2015.